Sosialisasi Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Dalam Upaya Pencegahan Perkawinan Usia Anak di Desa Tikonu Kecamatan Wundulako Kabupaten Kolaka - Mallapiseng, Arafat; Baso, Sudirman; Ferdiansyah; Malli, Lady Sisilia; Mawarni, Ayu; Ardita, Lola; Sari, Ratna (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Socialization of law number 16 of 2019 concerning marriage, especially the minimum age limit set at 19 years and the negative impacts it causes, was carried out in Tikonu village, Pomalaa sub-district, Kolaka district, with the aim of preventing child marriage (early marriage) as much as possible by provide knowledge and understanding to the public about the regulations issued by the government, especially regarding the minimum age requirement of 19 years for men and women who want to get married. This activity includes observations by the community service team of the FISIP-USN Kolaka public administration study program,delivery of material, and Focus Group Discussion (FGD). The results of the socialization found the fact that many people still do not know about the existence of regulations regarding the minimum age limit for men and women who wish to marry, and found 6 (six) cases of child marriage that had occurred in Tikonu village. The community service team is encouraging the creation of Kolakadistrict regional regulations as an operational basis for preventing child marriage in Kolaka district through the Women's Empowerment and Child Protection (DP3A) service.